SUBGLACIAL WATER LAYER AND GROUNDING LINE DERIVED FROM BACKSCATTERING COEFFICIENTS OF RADIO ECHO SOUNDING IN THE SHIRASE GLACIER AND ROI BAUDOUIN ICE SHELF, EAST ANTARCTICA - ニシオ, フミヒコ; ウラツカ, セイホ; NISHIO, Fumihiko; URATSUKA, Seiho (National Institute of Polar Research, 1991)
P(論文) In the 1986-87 austral summer, ice thickness measurements using a new designed airborne radio echo sounding system were carried out in the Shirase Glacier drainage basin and Roi Baudouin lce Shelf, Princess Ragnhild Coast, East Antarctica. The accurate determination of ice thickness during the flight was supported by measurements of surface elevation calibrated over the open sea at the beginning and end of each flight with radar altimetry. Location was determined by an OMEGA system and satellite Global Positioning System (GPS). The ice sheet profile along the flow line of the Shirase Glacier and ice shelf along the flight line from Asuka Camp to the Roi Baudouin Ice Shelf were determined and bottom features such as subglacier water layer and grounding line were clarified by finding the radio backscattering coefficients. The accurate surface elevation and backscattering coefficients obtained from the radar equation are adequate for locating the grounding line and detecting its accurate location within a few kilometers. It is also shown that the subglacial water layer was inferred from the backscattering coefficients of radio echo sounding along the Shirase Glacier flow line. The water layer thickness is estimated to be 0-30cm at the interface between the base of the ice sheet and the bedrock in the regions downstream of Shirase Glacier. departmental bulletin paper